ChemInform Abstract: Th(AsIII4AsV4O18): A Mixed‐Valent Oxoarsenic(III)/Arsenic(V) Actinide Compound Obtained under Extreme Conditions. Issue 43 (21st October 2014) - Yu, Na; Klepov, Vladislav V.; Kegler, Philip; Bosbach, Dirk; Albrecht‐Schmitt, Thomas E.; Alekseev, Evgeny V.
Abstract Crystals of Th(As8O18) are obtained along with an amorphous phase and CsAs3O8 by high‐temperature/high‐pressure reaction of Th(NO3)4·5H2O, As2O3, and CsNO3 in a ratio of 1:8:2 (Pt capsule, 3 GPa, 1200 °C; 0.2 °C/min cooling rate).